Silicon nitride fiber monolithic ceramic and method for preparing silicon nitride fiber monolithic ceramic based on wet spinning

Silicon nitride fiber monolithic ceramics were prepared through wet spinning technology, which solved the brittleness problem of silicon nitride ceramic materials, achieved synchronous improvement of the bending strength and fracture toughness of the material, and significantly improved the overall performance of the ceramic materials.

CN119710981AActive Publication Date: 2025-03-28HOHAI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411580828.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-28
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Due to the brittleness problem, silicon nitride ceramic materials are prone to cracks and fractures under stress states, which limits their application in aerospace, chemical and other fields.

Method used

Silicon nitride fiber monolithic ceramics are prepared by wet spinning technology. By mixing ceramic powder with anhydrous ethanol, ball milling, drying, grinding and sieving, spinning raw liquid is formed, and sprayed into a solidification bath through the spray head to solidify, obtaining a silicon nitride fiber precursor. Then, the immersion method is used to modify it in the interface layer slurry, pre-pressing molding, natural drying, glue discharge and hot pressing sintering, and obtain a silicon nitride fiber monolithic ceramic material with excellent bending strength and fracture toughness.

Benefits of technology

The simultaneous improvement of the bending strength and fracture toughness of silicon nitride ceramic materials is achieved. The comprehensive performance of the material is significantly excellent, and it can significantly improve fracture toughness without reducing the bending strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710981A_ABST
    Figure CN119710981A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of ceramic materials, and particularly relates to a silicon nitride fiber monolithic ceramic and a method for preparing the silicon nitride fiber monolithic ceramic based on wet spinning, and the method comprises the following steps: preparing a silicon nitride fiber monolithic precursor, carrying out silicon nitride fiber interface modification, carrying out pre-pressing molding, drying a green body, and discharging glue from the green body. The bending strength of the silicon nitride fiber monolithic ceramic can reach 580 MPa or above, and the fracture toughness of the silicon nitride fiber monolithic ceramic can reach 13 MPa.m < 1 / 2 > or above. The silicon nitride fiber is successfully prepared by adopting a wet spinning technology, the bending strength and the fracture toughness of the silicon nitride fiber monolithic ceramic material are effectively improved, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a ceramic material, in particular to a silicon nitride fiber monolithic ceramic and a method for preparing the silicon nitride fiber monolithic ceramic based on wet spinning. Background Art

[0002] Silicon nitride ceramics are an important structural ceramic material. They have excellent properties such as high thermal stability, strong antioxidant ability, high hardness, wear resistance, high temperature resistance and high product dimensional accuracy. They are widely used in aerospace, chemical industry, mechanical processing, biomedicine and other fields. With the rapid development of aerospace in recent years, silicon nitride ceramics have attracted the attention of many researchers and become the most promising material. However, its fatal weakness is brittleness. When it is under stress, it will produce cracks and even fractures, resulting in material failure, which limits its application in the above fields. This is one of the problems that need to be solved. Therefore, in order to ensure that silicon nitride materials maintain good reliability and safety during use, it is urgent to improve the brittleness of the material without reducing the material. With the further in-depth research of ceramic materials by the materials community, it is found that according to the current research ideas, in order to obtain higher performance, the structure and composition of the material must become more complex and difficult to control. Based on the inspiration of the special organizational structure of some biological materials in nature, the idea of ​​bionic structure design is introduced in the design and research of materials. In 1988, Coblenz proposed the idea of ​​fiber monolithic structure design. Fiber monolithic structure ceramic composite materials simulate the fiber structure characteristics of bamboo. First, the powder is made into a precursor of ceramic fiber, then a certain thickness of interface layer is coated on its surface, and then hot-pressed and sintered. Baskaran et al. prepared SiC / graphite fiber monolithic structure ceramics with a bending strength of 220 MPa and a fracture work of 1300 J / m 2 . Summary of the invention

[0003] In view of the shortcomings of the prior art, the present invention provides a silicon nitride fiber monolithic ceramic and a method for preparing silicon nitride fiber monolithic ceramic based on wet spinning. The process is simple, easy to operate, low in cost, and highly designable. The obtained silicon nitride fiber has excellent machinability. The prepared silicon nitride fiber monolithic ceramic material has excellent bending strength and fracture toughness, and has excellent comprehensive performance.

[0004] The technical solution provided by the present invention is as follows: The present invention provides a method for preparing silicon nitride fiber monolithic ceramics based on wet spinning, comprising the following steps: A ceramic powder containing silicon nitride, aluminum oxide and yttrium oxide is mixed with anhydrous ethanol, and a mixed powder is obtained after ball milling, drying, grinding and sieving, a mixed solution consisting of a dispersant, a binder, a plasticizer and an organic solvent is added, and the mixed powder is ball milled again to obtain a spinning solution, and then the spinning solution is sprayed into a coagulation bath through a nozzle, and a silicon nitride fiber precursor is obtained after coagulation; The silicon nitride fiber precursor is immersed in an interface layer slurry obtained by mixing boron nitride and aluminum oxide powders by an immersion method for modification, and the thickness of the interface layer is controlled by the immersion time to obtain a silicon nitride fiber precursor with an interface layer; The dried silicon nitride fiber precursor with the interface layer is cut according to the size of the pre-pressing mold, arranged uniaxially or crosswise in the mold, and then pre-pressed to obtain a fiber monolith pre-pressed green body; The fiber monolith pre-pressed green body is naturally dried; Debinding the dried green body; The debinding green body is hot pressed and sintered to obtain a silicon nitride fiber monolithic ceramic material.

[0005] Furthermore, the mass ratio of silicon nitride, aluminum oxide and yttrium oxide in the ceramic powder is 90-100:3-5:7-12, and the particle size of silicon nitride is 0.5 μm.

[0006] Furthermore, the binder is polyethylene glycol butyral, the dispersant is polyethylene glycol, the plasticizer is propylene glycol, the organic solvent is anhydrous ethanol, and the mass ratio of the binder, the dispersant, the plasticizer and the organic solvent is 10~20:10:3~5:70~75.

[0007] Furthermore, the coagulation bath is water, the temperature of the coagulation bath is 0-10° C., and the diameter of the obtained silicon nitride fiber precursor is 500-800 μm.

[0008] Furthermore, the boron nitride and aluminum oxide powders are mixed in a mass ratio of 1:3, and the particle size of the boron nitride is 1-5 μm.

[0009] Furthermore, the silicon nitride fiber precursor is immersed in the interface layer slurry for 10 to 15 minutes, and the thickness of the interface layer is 5 to 20 μm.

[0010] Furthermore, when a hydraulic press is used for pre-pressing, the pre-pressing pressure is 10-15 MPa and the holding time is 10-20 min.

[0011] Furthermore, the debinding conditions are as follows: heating from room temperature to 600-700 °C at a heating rate of 0.5-5.0 °C / min, and keeping the temperature for 1-2 h.

[0012] Furthermore, the sintering conditions are as follows: heating from room temperature to 1780~1800°C at a heating rate of 10~15°C / min, keeping the temperature for 1~2 h, and cooling with the furnace.

[0013] The present invention also provides a silicon nitride fiber monolithic ceramic, which is prepared according to the above method, and the silicon nitride fiber monolithic ceramic has a bending strength of 500-600 MPa and a fracture toughness of 10-15 MPa·m 1 / 2 .

[0014] Beneficial Effects

[0015] The present invention provides a method for preparing silicon nitride fiber monolithic ceramics based on wet spinning, which has a simple process and low cost, and achieves a simultaneous improvement in the strength and toughness of ceramic materials. The method for preparing silicon nitride fiber monolithic ceramic materials provided by the present invention greatly shortens the preparation time of the fiber, and the coating is evenly coated on the surface of the fiber precursor, which is more conducive to the deflection and bifurcation of cracks at the interface during the stress process, thereby improving the fracture toughness of the ceramic material. The silicon nitride fiber monolithic ceramic material finally obtained improves the fracture toughness of the material without reducing the bending strength.

[0016] Specifically, the present invention has the following outstanding advantages over the prior art:

[0017] (1) The silicon nitride fiber precursor is prepared by wet spinning technology. The process is simple, easy to operate, and low-cost, which greatly shortens the fiber preparation time and improves the preparation efficiency. The prepared silicon nitride fiber has a smooth and continuous surface, is easy to process and deform, has a diameter of 500~800 μm, has a certain toughness, and can be cut into various shapes, solving the problem of poor fluidity of the previously prepared fibers.

[0018] (2) When preparing the spinning solution, a certain amount of propylene glycol is added to increase the fluidity of the spinning solution. When the spinning solution enters the spinning nozzle and solidifies, it will not cause blockage. In addition, the prepared fiber has better toughness and is easier to process.

[0019] (3) The coagulation bath used in this method is water, and the temperature of the coagulation bath is room temperature, which greatly reduces the cost.

[0020] (4) The BN interface is evenly coated on the surface of the fiber precursor, which is more conducive to the deflection and bifurcation of cracks at the interface during the stress process, thereby improving the fracture toughness of the ceramic material.

[0021] (5) The flexural strength and fracture toughness of silicon nitride fiber monolithic ceramic materials prepared by this method reached 500~600 MPa and 10~15 MPa·m 1 / 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The scanning electron microscope pictures of the silicon nitride fiber precursor before and after coating in Example 1 of the present invention are shown. It can be seen that the surface of the silicon nitride fiber precursor is smooth, with a diameter of about 550 μm. After coating with BN, BN is evenly distributed on the surface of the silicon nitride fiber.

[0023] Figure 2 The microstructure of the Si3N4 / BN fiber monolith ceramic material after sintering in Example 1 of the present invention method. It can be found that the black phase is the Si3N4 cell body, the white phase around the Si3N4 cell body is the BN interface, and it can be found that the width of the Si3N4 cell body is about 450 μm, and the thickness of BN is about 10 μm. DETAILED DESCRIPTION

[0024] The present invention is further explained in detail below in conjunction with the accompanying drawings and specific embodiments, but it should be understood that the protection scope of the present invention is not limited to the specific embodiments.

[0025] The embodiment of the present invention provides a method for preparing silicon nitride fiber monolithic ceramics based on wet spinning, comprising the following steps: 1) Preparation of silicon nitride fiber precursor: ceramic powders containing silicon nitride, aluminum oxide and yttrium oxide are mixed with anhydrous ethanol, and mixed powders are obtained after ball milling, drying, grinding and sieving, and a mixed solution consisting of a dispersant, a binder, a plasticizer and an organic solvent is added, and the mixture is ball milled again to obtain a spinning solution, and then the spinning solution is sprayed into a coagulation bath through a nozzle, and the silicon nitride fiber precursor is obtained after coagulation; 2) Silicon nitride fiber interface modification: The silicon nitride fiber precursor is modified by the impregnation method, and the boron nitride and aluminum oxide powders are stirred in deionized water to obtain an interface layer slurry. The thickness of the interface layer is controlled by the immersion time to obtain a silicon nitride fiber precursor with an interface layer; 3) Pre-pressing: Cut the dried silicon nitride fiber precursor with the interface layer according to the size of the pre-pressing mold, arrange it uniaxially or crosswise in the mold, and then pre-press it to obtain a fiber monolith pre-pressed green body; 4) Green body drying: The fiber monolith pre-pressed green body is naturally dried; 5) Debinding of green body: Debinding of the dried green body; 6) Hot pressing and sintering: The debinding green body is hot pressed and sintered to obtain silicon nitride fiber monolithic ceramic material.

[0026] In this embodiment, step 1) is specifically as follows: first, silicon nitride, aluminum oxide and yttrium oxide are mixed with anhydrous ethanol in a mass ratio of 90-100:3-5:7-12, and a planetary ball mill is used for ball milling for 48 h to obtain a uniform wet mixed powder, and the wet mixed powder is dried using a rotary evaporator, and the dried mixed powder is ground and sieved to finally obtain a fine and uniform mixed powder, and a dispersant, a binder, a plasticizer and an organic solvent are mixed, and a mixed solution is obtained by mechanical stirring, and then the mixed powder is mixed with the solution in a mass ratio of 1:1, and ball milled for 48 h to obtain a spinning stock solution, which enters a coagulation bath through a spinning nozzle, and a silicon nitride fiber monolith precursor is obtained after coagulation, wherein the diameter of the silicon nitride fiber precursor is 500-800 μm, the curing agent is polyethylene glycol butyral, the binder is polyethylene glycol, the plasticizer is glycerol, and the coagulation bath is water.

[0027] In this embodiment, step 2) is specifically as follows: the silicon nitride fiber precursor is modified by an immersion method, firstly, boron nitride is mixed in deionized water, mechanically stirred for 3 hours, and then alumina powder is added, and stirring is continued for 6 hours to obtain a uniformly mixed interface layer slurry, wherein boron nitride and alumina are mixed in a mass ratio of 1:3, and the silicon nitride fiber monolith precursor is immersed in the interface layer slurry for 10 to 15 minutes, and the interface layer thickness of the fiber monolith precursor is changed by the immersion time, and the interface layer thickness is 5 to 20 μm.

[0028] In this embodiment, step 3) is specifically as follows: first, the impregnated fiber monolith precursor is dried in an oven at a drying temperature of 60°C, the impregnated silicon nitride fiber monolith fiber precursor is cut according to the size of the pre-pressing mold, and uniaxially or cross-arranged in the mold, and pre-pressed using a hydraulic press at room temperature, and maintained at a pressure of 10-20 MPa for 10-20 min to obtain a fiber monolith pre-pressed green body.

[0029] In this embodiment, step 4) is specifically as follows: placing the fiber monolith pre-pressed green body in a room for natural drying for 14 days, until the quality of the fiber monolith green body no longer changes, and the green body is dried.

[0030] In this embodiment, step 5) is specifically as follows: the dried green body is placed in a box-type resistance furnace for debinding, the debinding temperature is 600-700°C, the holding time is 1-5 h, and the heating rate is 0.5-5°C / min.

[0031] In this embodiment, step 6) is specifically as follows: the green body after debinding is hot pressed and sintered in a hot pressing sintering furnace, the temperature is increased to 1780~1800℃ at a heating rate of 10~15℃ / min, the holding time is 1~2h, the pressure is 30MPa, and the silicon nitride fiber monolithic ceramic material is obtained after cooling in the furnace.

[0032] This embodiment also provides a silicon nitride fiber monolithic ceramic, which is prepared according to the above method. The silicon nitride fiber monolithic ceramic has a bending strength of 500-600 MPa and a fracture toughness of 10-15 MPa·m 1 / 2 .

[0033] Example 1

[0034] A method for preparing silicon nitride fiber monolithic ceramics based on wet spinning comprises the following steps:

[0035] (1) Preparation of silicon nitride fiber precursor: first, 90g silicon nitride, 3g aluminum oxide and 7g yttrium oxide were mixed with anhydrous ethanol for wet mixing, and the slurry was ball milled for 48 hours using a ball mill, and then dried using a rotary evaporator. The dried powder was ground and sieved to obtain a fine and uniform mixed powder, and then a mixed solution of 10g polyethylene glycol butyral, 10g polyethylene glycol, 5g propylene glycol and 75g anhydrous ethanol was prepared, and mechanically stirred for 8 hours to fully dissolve the solution. After dissolution, the mixed powder was added, and the spinning solution was obtained after ball milling for 48 hours. The spinning solution was sprayed into a coagulation bath using a spinning nozzle, and the silicon nitride fiber precursor was obtained after soaking in the coagulation bath for 20 minutes. The coagulation bath was deionized water and the temperature was room temperature. The diameter of the silicon nitride fiber precursor was 550 μm.

[0036] (2) Silicon nitride interface modification: The silicon nitride fiber precursor was modified by the impregnation method. 3.75 g of boron nitride was mixed in deionized water and mechanically stirred for 3 h. Then, 1.25 g of alumina powder was added and stirred for 6 h to obtain a uniformly mixed interface layer slurry. Boron nitride and alumina were mixed in a mass percentage of 1:3. The silicon nitride fiber monolith precursor was immersed in the interface layer slurry for 10 min. The interface layer thickness of the fiber monolith precursor was changed by changing the immersion time. The thickness of the BN interface layer was 10.14 μm.

[0037] (3) Pre-pressing: First, the coated fiber monolith precursor is dried in an oven at a drying temperature of 60°C, and the impregnated silicon nitride fiber precursor is cut according to the size of the pre-pressing mold. The fibers are cut into fibers of uniform length, arranged uniaxially or crosswise in the mold, and pre-pressed at room temperature using a hydraulic press. The pre-pressed green body of the fiber monolith is obtained at 10 MPa for 20 min.

[0038] (4) Body drying: The fiber monolith pre-pressed body is placed in a room for natural drying for 14 days until the quality of the fiber monolith body no longer changes. The body drying is completed.

[0039] (5) Debinding of green body: The dried green body is placed in a box-type resistance furnace for debinding. The debinding temperature is 600 °C, the holding time is 1 h, and the heating rate is 0.5 °C / min.

[0040] (6) Hot pressing sintering: The debinding green body was hot pressed in a hot pressing sintering furnace. The temperature was raised to 1780 °C at a heating rate of 10 °C / min, the holding time was 1 h, and the pressure was 30 MPa. After cooling in the furnace, the silicon nitride fiber monolithic ceramic material was obtained. Its flexural strength and fracture toughness were 567.17 MPa and 11.76 MPa·m, respectively. 1 / 2 .

[0041] Example 2

[0042] A method for preparing silicon nitride fiber monolithic ceramics based on wet spinning comprises the following steps:

[0043] (1) Preparation of silicon nitride fiber precursor: first, 100g silicon nitride, 5g aluminum oxide and 12g yttrium oxide were mixed with anhydrous ethanol for wet mixing, and the slurry was ball milled for 48h using a ball mill, and then dried using a rotary evaporator. The dried powder was ground and sieved to obtain a fine and uniform mixed powder, and then a mixed solution of 15g polyethylene glycol butyral, 10g polyethylene glycol, 3g propylene glycol and 70g anhydrous ethanol was prepared, and mechanically stirred for 10h to fully dissolve the solution. After dissolution, the mixed powder was added, and ball milled for 48h to obtain a spinning solution, which was then introduced into a coagulation bath through a spinning nozzle. The spinning solution was sprayed into the coagulation bath using a spinning nozzle, and the silicon nitride fiber precursor was obtained after being soaked in the coagulation bath for 20min. The coagulation bath was deionized water and the temperature was room temperature. The diameter of the silicon nitride fiber precursor was 650 μm.

[0044] (2) Silicon nitride interface modification: The silicon nitride fiber precursor was modified by the impregnation method. 5.25 g of boron nitride was mixed in deionized water and mechanically stirred for 2 h. Then, 1.75 g of alumina powder was added and stirred for 8 h to obtain a uniformly mixed interface layer slurry. Boron nitride and alumina were mixed in a mass percentage of 1:3. The silicon nitride fiber monolith precursor was immersed in the interface layer slurry for 15 min. The interface layer thickness of the fiber monolith precursor was changed by changing the immersion time. The thickness of the BN interface layer was 12.57 μm.

[0045] (3) Pre-pressing: First, the coated fiber monolith precursor is dried in an oven at a drying temperature of 60°C, and the impregnated silicon nitride fiber precursor is cut according to the size of the pre-pressing mold. The fibers are cut into fibers of uniform length, arranged uniaxially or crosswise in the mold, and pre-pressed at room temperature using a hydraulic press. The pressure is maintained at 15 MPa for 20 min to obtain a fiber monolith pre-pressed green body.

[0046] (4) Body drying: The fiber monolith pre-pressed body is placed in a room for natural drying for 14 days until the quality of the fiber monolith body no longer changes. The body drying is completed.

[0047] (5) Debinding of green body: The dried green body is placed in a box-type resistance furnace for debinding. The debinding temperature is 600 °C, the holding time is 1 h, and the heating rate is 2.0 °C / min.

[0048] (6) Hot pressing sintering: The debinding green body was hot pressed in a hot pressing sintering furnace. The temperature was raised to 1800 °C at a heating rate of 15 °C / min, the holding time was 1.5 h, and the pressure was 30 MPa. After cooling in the furnace, the silicon nitride fiber monolithic ceramic material was obtained. Its flexural strength and fracture toughness were 589.32 MPa and 13.93 MPa·m, respectively. 1 / 2 .

[0049] Example 3

[0050] A method for preparing silicon nitride fiber monolithic ceramics based on wet spinning comprises the following steps:

[0051] (1) Preparation of silicon nitride fiber precursor: 90 g of silicon nitride, 3 g of aluminum oxide and 7 g of yttrium oxide were wet mixed with anhydrous ethanol, and the slurry was ball milled for 48 h using a ball mill, and then dried using a rotary evaporator. The dried powder was ground and sieved to obtain a fine and uniform mixed powder. 20 g of polyethylene glycol butyral, 10 g of polyethylene glycol, and 5 g of propylene glycol were mixed with 75 g of anhydrous ethanol and mechanically stirred for 6 h to fully dissolve the solution. After dissolution, the mixed powder was added and ball milled for 48 h to obtain a spinning solution. The spinning solution was sprayed into a coagulation bath using a spinning nozzle. After soaking in the coagulation bath for 20 min, a silicon nitride fiber precursor was obtained. The coagulation bath was deionized water and the temperature was room temperature. The diameter of the silicon nitride fiber precursor was 700 μm.

[0052] (2) Silicon nitride interface modification: The silicon nitride fiber precursor was modified by the impregnation method. 6.75 g of boron nitride was mixed in deionized water and mechanically stirred for 4 h. Then, 2.25 g of alumina powder was added and stirred for 8 h to obtain a uniformly mixed interface layer slurry. Boron nitride and alumina were mixed in a mass percentage of 1:3. The silicon nitride fiber monolith precursor was immersed in the interface layer slurry for 20 min. The interface layer thickness of the fiber monolith precursor was changed by changing the immersion time. The thickness of the BN interface layer was 16.32 μm.

[0053] (3) Pre-pressing: First, the coated fiber monolith precursor is dried in an oven at a drying temperature of 70°C, and the impregnated silicon nitride fiber precursor is cut according to the size of the pre-pressing mold. The fibers are cut into fibers of uniform length, arranged uniaxially or crosswise in the mold, and pre-pressed at room temperature using a hydraulic press. The pressure is maintained at 15 MPa for 10 min to obtain a fiber monolith pre-pressed green body.

[0054] (4) Body drying: The fiber monolith pre-pressed body is placed in a room for natural drying for 14 days until the quality of the fiber monolith body no longer changes. The body drying is completed.

[0055] (5) Debinding of green body: The dried green body is placed in a box-type resistance furnace for debinding. The debinding temperature is 600 °C, the holding time is 2 h, and the heating rate is 5.0 °C / min.

[0056] (6) Hot pressing sintering: The debinding green body was hot pressed in a hot pressing sintering furnace. The temperature was raised to 1800 °C at a heating rate of 10 °C / min, and the holding time was 2 h. The pressure was 30 MPa. After cooling in the furnace, the silicon nitride fiber monolithic ceramic material was obtained. Its flexural strength and fracture toughness were 520.39 MPa and 14.65 MPa·m, respectively. 1 / 2 .

[0057] Table 1 shows the performance parameters of silicon nitride fiber monolithic ceramics in embodiments 1, 2 and 3 of the method of the present invention.

[0058] Table 1

[0059]

[0060] It can be seen from the above table that when the sintering temperature is higher, the mechanical properties of the prepared ceramics are better. When the sintering temperature is 1800 ℃ and the holding time is 1.5 h, the prepared silicon nitride / boron nitride fiber monolithic ceramics have excellent bending strength and fracture toughness. When the thickness of the BN interface layer is thicker, the fracture toughness increases, but the bending strength decreases.

[0061] Figure 2 This is the microstructure of the Si3N4 / BN fiber monolithic ceramic material after sintering in Example 1 of the method of the present invention. Figure 2 a is the microscopic morphology of the longitudinal section of the ceramic. It can be found that the black phase is the Si3N4 cell body, and the white phase around the Si3N4 cell body is the BN interface. It can be found that the width of the Si3N4 cell body is about 450 μm. In order to analyze the thickness of the BN interface layer, Figure 2 The rectangular box in a is enlarged, such as Figure 2 b. The thickness of BN was determined to be approximately 10 μm. Figure 2Scan the line in the direction of the blue arrow in b, and the result is as follows Figure 2 c. Figure 2 It was found in c that the content of Si element was the lowest when the content of BN element was the highest, which indicated that the interface in the middle was BN. Figure 2 (d and e) are transmission bright field images and high-resolution images, confirming the presence of silicon nitride and boron nitride through morphology and interplanar spacing. Figure 2 Scan the positions of A and B in d, and the results are as follows Figure 2 As shown. It is found that A is boron nitride and B is silicon nitride. Figure 2 The results of f are used to prove Figure 2 (d and e) Results.

[0062] The above are only preferred embodiments of the present invention, and the present invention is not limited to the contents of the embodiments. For those skilled in the art, various changes and modifications can be made within the scope of the technical solution of the present invention, and any changes and modifications made are within the protection scope of the present invention.

Claims

1. A method for preparing silicon nitride fiber monolithic ceramics based on wet spinning, characterized in that: The following steps are involved: A ceramic powder containing silicon nitride, aluminum oxide and yttrium oxide is mixed with anhydrous ethanol, and a mixed powder is obtained after ball milling, drying, grinding and sieving, a mixed solution consisting of a dispersant, a binder, a plasticizer and an organic solvent is added, and the mixed powder is ball milled again to obtain a spinning solution, and then the spinning solution is sprayed into a coagulation bath through a nozzle, and a silicon nitride fiber precursor is obtained after coagulation; The silicon nitride fiber precursor is immersed in an interface layer slurry obtained by mixing boron nitride and aluminum oxide powders by an immersion method for modification, and the thickness of the interface layer is controlled by the immersion time to obtain a silicon nitride fiber precursor with an interface layer; The dried silicon nitride fiber precursor with the interface layer is cut according to the size of the pre-pressing mold, arranged uniaxially or crosswise in the mold, and then pre-pressed to obtain a fiber monolith pre-pressed green body; The fiber monolith pre-pressed green body is naturally dried; Debinding the dried green body; The debinding green body is hot pressed and sintered to obtain a silicon nitride fiber monolithic ceramic material.

2. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: The mass ratio of silicon nitride, aluminum oxide and yttrium oxide in the ceramic powder is 90-100:3-5:7-12, and the particle size of silicon nitride is 0.5 μm.

3. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: The binder is polyethylene glycol butyral, the dispersant is polyethylene glycol, the plasticizer is propylene glycol, the organic solvent is anhydrous ethanol, and the mass ratio of the binder, the dispersant, the plasticizer and the organic solvent is 10-20:10:3-5:70-75.

4. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: The coagulation bath is water, the temperature of the coagulation bath is 0-10° C., and the diameter of the obtained silicon nitride fiber precursor is 500-800 μm.

5. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: The boron nitride and aluminum oxide powders are mixed in a mass ratio of 1:3, and the particle size of the boron nitride is 1-5 μm.

6. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: The silicon nitride fiber precursor is immersed in the interface layer slurry for 10 to 15 minutes, and the thickness of the interface layer is 5 to 20 μm.

7. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: When using a hydraulic press for pre-pressing, the pre-pressing pressure is 10~15MPa and the holding time is 10~20min.

8. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: The debinding conditions are as follows: heating from room temperature to 600 ~700 ℃ at a heating rate of 0.5 ~ 5.0 ℃ / min, and keeping warm for 1 ~ 2 h.

9. The method for preparing silicon nitride fiber monolithic ceramics based on wet spinning according to claim 1, characterized in that: The sintering conditions are as follows: heating from room temperature to 1780~1800 ℃ at a heating rate of 10~15 ℃ / min, keeping the temperature for 1~2 h, and cooling with the furnace.

10. A silicon nitride fiber monolithic ceramic, characterized in that: The silicon nitride fiber monolithic ceramic is prepared according to the method according to any one of claims 1 to 9, wherein the bending strength of the silicon nitride fiber monolithic ceramic is 500-600 MPa and the fracture toughness is 10-15 MPa·m 1 / 2 .

Citation Information

Patent Citations

  • Wet spinning-impregnation method for preparing double-interface fiber monolith zirconium boride composite material

    CN111892407A

  • Preparation method of silicon nitride-based fiber monolithic ceramic wave-transmitting material

    CN112898038A

  • Silicon nitride fiber reinforced wave-transparent ceramic material and preparation method thereof

    CN115448732A

  • Boron carbide ceramic fibers

    US20090318280A1

  • Carbonaceous fiber reinforced composites

    US4868038A